High-temperature-resistant and anti-pollution ZIF-8 / PI nano composite filter material and preparation method thereof
Through electrospinning technology, ZIF-8 nanoparticles and PI were combined to develop high-temperature and pollution-resistant ZIF-8/PI nanocomposite filter material, which solved the problem of degradation in traditional materials in high-temperature environments and achieved high-efficiency filtration and anti-pollution properties, suitable for industrial applications and simplify production processes.
Patent Information
- Application Number
- CN202411387021.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-31
AI Technical Summary
Traditional filter materials have deteriorated performance in high temperature environments and cannot meet the high industrial standards. The existing technology faces the challenges of complex preparation, high cost and large-scale production when combining MOFs materials with nanofiber membranes.
Develop a high temperature and pollution-resistant ZIF-8/PI nanocomposite filter material. The ZIF-8 nanoparticles are combined with PI through electrospinning technology, and a simplified preparation process is used to utilize the high temperature resistance and ZIF- 8 has the advantages of high specific surface area and pore regulation to form nanocomposite materials with high chemical stability and anti-pollution properties.
It significantly improves the stability and durability of materials in extreme industrial environments, improves the capture efficiency of fine particulate matter such as PM2.5, simplifies production processes, reduces costs, and is suitable for industrial flue gas treatment and air purification systems. And has antibacterial properties.
Smart Images

Figure CN119221209A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano composite materials, and particularly relates to a high temperature resistant and pollution resistant ZIF-8 / PI nano composite filter material and a preparation method thereof. Background Art
[0002] With the acceleration of industrialization, air pollution is becoming increasingly serious, and tiny particles such as PM0.3 pose a huge threat to human health and the environment. Traditional filter materials have limitations in filtration efficiency and high temperature resistance, especially in high temperature environments, their performance decreases significantly and cannot meet the high standards of modern industry.
[0003] To solve this problem, researchers have been exploring new filter materials. Chinese Patent No. 201810719982.8 describes an innovative method for preparing multilayer filter materials, which uses electrospinning technology combined with specific chemical treatment. Through electrospinning of two PAA solutions, a thermally stable fiber layer was formed, and the material performance was further improved by thermal imidization treatment, showing good filtration efficiency. However, despite the excellent performance of this technology in filtration efficiency, the potential of integrating MOFs materials into filtration structures to utilize their high specific surface area and adjustable pore size has not yet been explored.
[0004] Chinese patent No. 202311137888.9 discloses a CS@ZIF-8 / PLA composite electrospun fiber membrane that combines the properties of polylactic acid and chitosan. This material not only has biodegradability and antibacterial properties, but also has high filtration efficiency and strong chemical stability, but it is difficult to adapt to extreme industrial environments, and the existing technology faces the challenges of complex preparation, high cost and difficulty in large-scale production when combining MOFs materials with nanofiber membranes. Summary of the invention
[0005] In view of the limitations of existing technologies, this patent combines ZIF-8 nanoparticles with PI to develop a nanocomposite filter material that is resistant to high temperatures, has high chemical stability and anti-pollution properties. This material not only inherits the advantages of high specific surface area and pore regulation of MOFs, but also significantly improves the stability and durability in extreme industrial environments through the high temperature resistance of PI. In addition, the preparation process of this patent simplifies the production process, reduces costs, and meets the urgent demand for high-performance filter materials in industrial applications.
[0006] To achieve the above object, the present invention provides a high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof, characterized in that the specific steps include:
[0007] A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof, comprising the following steps:
[0008] (1) Synthesis of ZIF-8: Dissolve zinc nitrate hexahydrate (Zn(NO3)2·6H2O) in a solvent and 2-methylimidazole in a corresponding solvent. Mix well, stir for 20 minutes and let stand at room temperature. Centrifuge the solution three times, wash with anhydrous methanol and dry in a vacuum oven at 80-120°C for 24 hours to obtain white powder ZIF-8;
[0009] (2) Preparation of spinning solution: Disperse ZIF-8 powder into N,N-dimethylformamide solvent to prepare the first solution, then add ODA and stir to dissolve to form the second solution. Next, dissolve dianhydride monomer powder in the mixed solution to ensure that the monomer is fully reacted, and let stand for 6 hours to obtain ZIF-8 / PAA precursor solution;
[0010] (3) Preparation of ZIF-8 / PAA nanofibers: Add the ZIF-8 / PAA precursor solution obtained by standing still into a syringe, and form a ZIF-8 / PAA nanofiber layer on a needle-punched felt base fabric by an electrospinning method;
[0011] (4) Imidization: The prepared ZIF-8 / PAA nanocomposite filter material was placed in an electric heated forced air drying oven at 80°C for 1 h to remove the solvent, and then the membrane was transferred to a muffle furnace. The thermal imidization process of the ZIF-8 / PAA nanofiber membrane was completed in two stages to obtain the PI nanocomposite filter material.
[0012] Preferably, in step (1), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:2-8, the solvent is at least one of methanol, ethanol and water; and the rotation speed during the stirring reaction is 300-600 rpm.
[0013] Preferably, the centrifugal speed in step (1) is 8000-10000 rpm, the centrifugal time is 10 min, the solvent during the washing process is of the same polarity, and the number of washing times is greater than or equal to 3 times.
[0014] Preferably, in step (2), the molar ratio of ODA to dianhydride monomer is 1:1-1.02, and the dianhydride monomer is added to the stirred and uniformly dissolved second solution in 8-10 times, and the amount added decreases with the increase of the number of times, and each time the added dianhydride monomer powder is added, it is necessary to wait until the added dianhydride monomer powder is completely dissolved before adding the next time, and the interval time is about 10-20 minutes.
[0015] Preferably, the dianhydride monomer in step (2) is one of PMDA, BPDA and ODPA.
[0016] Preferably, in the step (2), by controlling the mass ratio of ZIF-8 to PMDA, a precursor solution ZIF-8 / PAA with a doping amount of 1%-8% is prepared.
[0017] Preferably, the electrospinning conditions in step (3) are: spinning voltage of 18-35 kV, drum speed of 100-200 r / min, distance from needle tip to receiver of 10-20 cm, pushing speed of 0.001-0.01 mm / s, ambient temperature of 20-30° C., and relative humidity of 20-60%.
[0018] Preferably, the concentration of the spinning solution in step (3) is 10-30%, and the syringe nozzle is 18G.
[0019] Preferably, the needle-punched felt base fabric in step (3) is one or a mixture of basalt fiber, glass fiber, polyimide, and polyetheretherketone fiber.
[0020] Preferably, in the step (4), the first stage thermal imidization treatment is carried out at 100-200° C. for 20-40 min, and the PAA molecules are dehydrated and cyclized into PI; the second amidation heat treatment temperature is 200-300° C. for 15-30 min, and the imidization is completed.
[0021] Compared with the prior art, the beneficial effects of the present invention are: (1) the use of high temperature resistant needle-punched felt as the supporting matrix material can not only protect the nanofibers, but also fine-tune the nanofiber membrane, so that the composite filter material can maintain structural stability and unchanged performance under extreme environments such as high temperature; (2) compared with the 201810719982.8 patent, by introducing the ZIF-8 nanostructure, the filter material of the present invention exhibits super anti-pollution, which helps to prevent the adhesion of moisture and pollutants, thereby reducing the maintenance requirements of the filter material and extending its service life; (3) the addition of the ZIF-8 nanocomposite structure effectively refines the diameter of the PI fiber and increases the electrostatic effect between the fibers. These improvements work together to significantly improve the material's capture efficiency of fine particles such as PM2.5. (4) Compared with Patent No. 202311137888.9, the preparation process of the method of the present invention is simple and efficient, and significantly improves the temperature resistance and chemical resistance of the material, making it more suitable for extreme industrial environments; (5) The filter material of the present invention is not only suitable for industrial flue gas treatment and air purification systems due to its excellent versatility, but its specially designed electrostatically blended ZIF-8 / PI structure also has antibacterial properties, which broadens its application potential in multiple fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 SEM photo and diameter distribution diagram of PI nanofiber membrane.
[0023] Figure 2 SEM image and diameter distribution diagram of ZIF-8 / PI nanofiber membrane.
[0024] Figure 3 This is a droplet contact angle diagram for preparing anti-pollution composite filter material. DETAILED DESCRIPTION
[0025] The present invention is described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0026] Example 1
[0027] A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof, characterized in that the material comprises the following steps:
[0028] (1) Synthesis of ZIF-8: Dissolve zinc nitrate hexahydrate (Zn(NO3)2·6H2O) in a solvent and 2-methylimidazole in a corresponding solvent. Mix well, stir for 20 minutes and let stand at room temperature. Centrifuge the solution three times, wash with anhydrous methanol and dry in a vacuum oven at 80-120°C for 24 hours to obtain white powder ZIF-8;
[0029] (2) Preparation of spinning solution: Disperse ZIF-8 powder into N,N-dimethylformamide solvent to prepare the first solution, then add ODA and stir to dissolve to form the second solution. Next, dissolve dianhydride monomer powder in the mixed solution to ensure that the monomer is fully reacted, and let stand for 6 hours to obtain ZIF-8 / PAA precursor solution;
[0030] (3) Preparation of ZIF-8 / PAA nanofibers: Add the ZIF-8 / PAA precursor solution obtained by standing still into a syringe, and form a ZIF-8 / PAA nanofiber layer on a needle-punched felt base fabric by an electrospinning method;
[0031] (4) Imidization: The prepared ZIF-8 / PAA nanocomposite filter material was placed in an electric heated forced air drying oven at 80°C for 1 h to remove the solvent, and then the membrane was transferred to a muffle furnace. The thermal imidization process of the ZIF-8 / PAA nanofiber membrane was completed in two stages to obtain the PI nanocomposite filter material.
[0032] Preferably, in step (1), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:8, the solvent is methanol, and the rotation speed during the stirring reaction is 400 rpm.
[0033] Preferably, the centrifugal speed in step (1) is 8000 rpm, the centrifugal time is 10 min, the solvent in the washing process is of the same polarity, and the washing is performed 3 times.
[0034] Preferably, in step (2), the molar ratio of ODA to dianhydride monomer is 1:1.02, and the dianhydride monomer is added to the stirred and uniformly dissolved second solution in 8-10 times, and the amount added decreases with the increase of the number of times, and each time the added dianhydride monomer powder is added, it is necessary to wait until the added dianhydride monomer powder is completely dissolved before adding the next time, and the interval time is about 15 minutes.
[0035] Preferably, the dianhydride monomer in step (2) is PMDA.
[0036] Preferably, in the step (2), by controlling the mass ratio of ZIF-8 to PMDA, a precursor solution ZIF-8 / PAA with a doping amount of 1% is prepared.
[0037] Preferably, the electrospinning conditions in step (3) are: spinning voltage of 30 kV, drum speed of 200 r / min, distance from needle tip to receiver of 16 cm, pushing speed of 0.001 mm / s, ambient temperature of 25±°C, and relative humidity of 30±%.
[0038] Preferably, the concentration of the spinning solution in step (3) is 26%, and the syringe nozzle is 18G.
[0039] Preferably, the needle-punched felt base fabric in step (3) is: glass fiber needle-punched felt.
[0040] Preferably, in the step (4), the first stage thermal imidization treatment is carried out at 100° C. for 30 min, and the PAA molecules are dehydrated and cyclized into PI; the second amidation heat treatment temperature is 200° C. for 30 min, and the imidization is completed.
[0041] The ZIF-8 / PI nanocomposite filter material of the present invention achieves a high efficiency of 98.9% and a low resistance of 40 Pa when filtering 2.5 micron particles. The synergistic effect of the composite material improves the overall performance, and the needle-punched felt base cloth enhances the mechanical strength and stability while protecting the material from damage. The material can operate stably at a high temperature above 240°C, showing its wide application prospects in industrial flue gas purification.
[0042] Example 2
[0043] A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof, comprising the following steps:
[0044] (1) Synthesis of ZIF-8: Dissolve zinc nitrate hexahydrate (Zn(NO3)2·6H2O) in a solvent and 2-methylimidazole in a corresponding solvent. Mix well, stir for 20 minutes and let stand at room temperature. Centrifuge the solution three times, wash with anhydrous methanol and dry in a vacuum oven at 80-120°C for 24 hours to obtain white powder ZIF-8;
[0045] (2) Preparation of spinning solution: Disperse ZIF-8 powder into N,N-dimethylformamide solvent to prepare the first solution, then add ODA and stir to dissolve to form the second solution. Next, dissolve dianhydride monomer powder in the mixed solution to ensure that the monomer is fully reacted, and let stand for 6 hours to obtain ZIF-8 / PAA precursor solution;
[0046] (3) Preparation of ZIF-8 / PAA nanofibers: Add the ZIF-8 / PAA precursor solution obtained by standing still into a syringe, and form a ZIF-8 / PAA nanofiber layer on a needle-punched felt base fabric by an electrospinning method;
[0047] (4) Imidization: The prepared ZIF-8 / PAA nanocomposite filter material was placed in an electric heated forced air drying oven at 80°C for 1 h to remove the solvent, and then the membrane was transferred to a muffle furnace. The thermal imidization process of the ZIF-8 / PAA nanofiber membrane was completed in two stages to obtain the PI nanocomposite filter material.
[0048] Preferably, in step (1), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:8, the solvent is water, and the rotation speed during the stirring reaction is 500 rpm.
[0049] Preferably, the centrifugal speed in step (1) is 8000 rpm, the centrifugal time is 10 min, the solvent in the washing process is of the same polarity, and the washing is performed 3 times.
[0050] Preferably, in step (2), the molar ratio of ODA to dianhydride monomer is 1:1.02, and the dianhydride monomer is added to the stirred and uniformly dissolved second solution in 8-10 times, and the amount added decreases with the increase of the number of times, and each time the added dianhydride monomer powder is added, it is necessary to wait until the added dianhydride monomer powder is completely dissolved before adding the next time, and the interval time is about 20 minutes.
[0051] Preferably, the dianhydride monomer in step (2) is BPDA.
[0052] Preferably, in the step (2), by controlling the mass ratio of ZIF-8 to PMDA, a precursor solution ZIF-8 / PAA with a doping amount of 3% is prepared.
[0053] Preferably, the electrospinning conditions in step (3) are: spinning voltage of 25 kV, drum speed of 150 r / min, distance from needle tip to receiver of 18 cm, pushing speed of 0.001 mm / s, ambient temperature of 25±°C, and relative humidity of 30±%.
[0054] Preferably, the concentration of the spinning solution in step (3) is 24%, and the syringe nozzle is 18G.
[0055] Preferably, the needle-punched felt base fabric in step (3) is: polyimide fiber needle-punched felt.
[0056] Preferably, in the step (4), the first stage thermal imidization treatment is carried out at 140° C. for 25 min, and the PAA molecules are dehydrated and cyclized into PI; the second amidation heat treatment temperature is 220° C. for 30 min, and the imidization is completed.
[0057] The ZIF-8 / PI nanocomposite filter material prepared by the present invention has a filtration efficiency of 99.6% for 2.5 micron particles, while maintaining a low resistance loss of 46 Pa. This composite material achieves complementary and improved performance through the combination of ZIF-8 and PI. The use of needle-punched felt base cloth not only provides additional mechanical strength for the material, but also enhances its overall stability and ensures the durability of the material.
[0058] Example 3
[0059] A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof, comprising the following steps:
[0060] (1) Synthesis of ZIF-8: Dissolve zinc nitrate hexahydrate (Zn(NO3)2·6H2O) in a solvent and 2-methylimidazole in a corresponding solvent. Mix well, stir for 20 minutes and let stand at room temperature. Centrifuge the solution three times, wash with anhydrous methanol and dry in a vacuum oven at 80-120°C for 24 hours to obtain white powder ZIF-8;
[0061] (2) Preparation of spinning solution: Disperse ZIF-8 powder into N,N-dimethylformamide solvent to prepare the first solution, then add ODA and stir to dissolve to form the second solution. Next, dissolve dianhydride monomer powder in the mixed solution to ensure that the monomer is fully reacted, and let stand for 6 hours to obtain ZIF-8 / PAA precursor solution;
[0062] (3) Preparation of ZIF-8 / PAA nanofibers: Add the ZIF-8 / PAA precursor solution obtained by standing still into a syringe, and form a ZIF-8 / PAA nanofiber layer on a needle-punched felt base fabric by an electrospinning method;
[0063] (4) Imidization: The prepared ZIF-8 / PAA nanocomposite filter material was placed in an electric heated forced air drying oven at 80°C for 1 h to remove the solvent, and then the membrane was transferred to a muffle furnace. The thermal imidization process of the ZIF-8 / PAA nanofiber membrane was completed in two stages to obtain the PI nanocomposite filter material.
[0064] Preferably, in step (1), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:8, the solvent is methanol, and the rotation speed during the stirring reaction is 300 rpm.
[0065] Preferably, the centrifugal speed in step (1) is 8000 rpm, the centrifugal time is 10 min, the solvent in the washing process is of the same polarity, and the washing is performed 3 times.
[0066] Preferably, in step (2), the molar ratio of ODA to dianhydride monomer is 1:1.02, and the dianhydride monomer is added to the stirred and uniformly dissolved second solution in 8-10 times, and the amount added decreases with the increase of the number of times, and each time the added dianhydride monomer powder is added, it is necessary to wait until the added dianhydride monomer powder is completely dissolved before adding the next time, and the interval time is about 20 minutes.
[0067] Preferably, the dianhydride monomer in step (2) is one of ODPA.
[0068] Preferably, in the step (2), by controlling the mass ratio of ZIF-8 to PMDA, a precursor solution ZIF-8 / PAA with a doping amount of 6% is prepared.
[0069] Preferably, the electrospinning conditions in step (3) are: spinning voltage of 20 kV, drum speed of 200 r / min, distance from needle tip to receiver of 16 cm, pushing speed of 0.001 mm / s, ambient temperature of 25±°C, and relative humidity of 30±%.
[0070] Preferably, the concentration of the spinning solution in step (3) is 26%, and the syringe nozzle is 18G.
[0071] Preferably, the needle-punched felt base fabric in step (3) is: basalt fiber needle-punched felt.
[0072] Preferably, in the step (4), the first stage thermal imidization treatment is carried out at 180° C. for 30 min, and the PAA molecules are dehydrated and cyclized to PI; the second amidation heat treatment temperature is 240° C. for 30 min, and the imidization is completed.
[0073] The patented ZIF-8 / PI nanocomposite filter material has an efficiency of up to 99% in filtering 2.5 micron particles and a resistance of only 43 Pa. This synthetic material has shown significant performance enhancement thanks to the fusion of ZIF-8 and PI. The addition of needle felt base fabric not only gives the material higher mechanical strength, but also improves its overall stability and durability.
[0074] In the above embodiments, more efficient filtering performance can be achieved by changing the ratio and concentration of the polymer in the spinning solution and the parameters of the electrospinning process. However, the protection scope of the present invention is not limited thereto. Any simple modification, change and equivalent structural change made to the above embodiments according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof, characterized in that: The following steps are involved: (1) Synthesis of ZIF-8: Dissolve zinc nitrate hexahydrate (Zn(NO3)2·6H2O) in a solvent and 2-methylimidazole in a corresponding solvent. Mix well, stir for 20 minutes and let stand at room temperature. Centrifuge the solution three times, wash with anhydrous methanol and dry in a vacuum oven at 80-120°C for 24 hours to obtain white powder ZIF-8; (2) Preparation of spinning solution: Disperse ZIF-8 powder into N,N-dimethylformamide solvent to prepare the first solution, then add ODA and stir to dissolve to form the second solution. Next, dissolve dianhydride monomer powder in the mixed solution to ensure that the monomer is fully reacted, and let stand for 6 hours to obtain ZIF-8 / PAA precursor solution; (3) Preparation of ZIF-8 / PAA nanofibers: Adding the ZIF-8 / PAA precursor solution obtained by standing still as described above into a syringe, and forming a ZIF-8 / PAA nanofiber layer on a needle-punched felt base fabric by an electrospinning method; (4) Imidization: The prepared ZIF-8 / PAA nanocomposite filter material was placed in an electric heated forced air drying oven at 80°C for 1 h to remove the solvent, and then the membrane was transferred to a muffle furnace. The thermal imidization process of the ZIF-8 / PAA nanofiber membrane was completed in two stages to obtain the PI nanocomposite filter material.
2. A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof according to claim 1, characterized in that: In the step (1), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:2-8, the solvent is at least one of methanol, ethanol and water; and the rotation speed during the stirring reaction is 300-600 rpm.
3. A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof according to claim 1, characterized in that: In the step (1), the centrifugal speed is 8000-10000 rpm, the centrifugal time is 10 min, the solvent in the washing process is of the same polarity, and the number of washing times is greater than or equal to 3 times.
4. A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof according to claim 1, characterized in that: In the step (2), the molar ratio of ODA to dianhydride monomer is 1:1-1.
02. The dianhydride monomer is added to the stirred and uniformly dissolved second solution in 8-10 times. The amount added decreases with the increase in the number of times. Each time, the dianhydride monomer powder added needs to be completely dissolved before the next addition. The interval time is about 10-20 minutes.
5. A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof according to claim 1, characterized in that: In the step (2), the dianhydride monomer is one of PMDA, BPDA and ODPA.
6. A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof according to claim 1, characterized in that: In the step (2), the mass ratio of ZIF-8 to PMDA is controlled to prepare a precursor solution ZIF-8 / PAA with a doping amount of 1% to 8%.
7. A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof according to claim 1, characterized in that: The electrospinning conditions in step (3) are as follows: spinning voltage is 18-35 kV, drum speed is 100-200 r / min, distance from needle tip to receiver is 10-20 cm, pushing speed is 0.001-0.01 mm / s, ambient temperature is 20-30° C., and relative humidity is 20-60%.
8. A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof according to claim 1, characterized in that: The needle-punched felt base fabric in step (3) is one or a mixture of basalt fiber, glass fiber, polyimide, and polyetheretherketone fiber.
9. A high temperature resistant and pollution resistant ZIF-8 / PI nanocomposite filter material and a preparation method thereof according to claim 1, characterized in that: In the step (4), the first stage of thermal imidization treatment is at 100-200° C. and kept warm for 20-40 minutes, and the PAA molecules are dehydrated and cyclized into PI; the second stage of thermal amidation treatment is at 200-300° C. and kept warm for 15-30 minutes, and the imidization is completed.
Citation Information
Patent Citations
Tree-shaped mixed matrix film constructed by two-component nano additive and preparation method and application thereof
CN110327792A
MOFs mixed matrix filtering material for sewage treatment and preparation method thereof
CN111888949A
Efficient air filtration composite nanofiber membrane and preparation method thereof
CN113368712A
MOF-polyimide composite fiber membrane as well as preparation method and application thereof
CN118257065A
Preparation method of ZIF-8 modified high-temperature-resistant composite nanofiber membrane
CN118650945A
